Superior Survival Outcomes of a Polyethylene Glycol-20k Based Resuscitation Solution in a Preclinical Porcine Model of Lethal Hemorrhagic Shock. Issue 5 (8th May 2022) - Khoraki, Jad; Wickramaratne, Niluka; Kang, Hae Sung; Xu, Haoxuan; Archambault, Caitlin; Blocher, Charles; Li, Ru; Liebrecht, Loren; Aboutanos, Michel; Mangino, Martin J.
Abstract : Objective: To compare early outcomes and 24-hour survival after LVR with the novel polyethylene glycol-20k-based crystalloid (PEG-20k), WB, or hextend in a preclinical model of lethal HS. Background: Posttraumatic HS is a major cause of preventable death. current resuscitation strategies focus on restoring oxygen-carrying capacity (OCC) and coagulation with blood products. Our lab shows that PEG-20k is an effective non-sanguineous, LVR solution in acute models of HS through mechanisms targeting cell swelling-induced microcirculatory failure. Methods: Male pigs underwent splenectomy followed by controlled hemorrhage until lactate reached 7.5–8.5 mmol/L. They were randomized to receive LVR with PEG-20k, WB, or Hextend. Surviving animals were recovered 4 hours post-LVR. Outcomes included 24-hour survival rates, mean arterial pressure, lactate, hemoglobin, and estimated intravascular volume changes. Results: Twenty-four-hour survival rates were 100%, 16.7%, and 0% in the PEG-20k, WB, and Hextend groups, respectively ( P = 0.001). PEG-20k significantly restored mean arterial press, intravascular volume, and capillary perfusion to baseline, compared to other groups. This caused complete lactate clearance despite decreased OCC. Neurological function was normal after next-day recovery in PEG-20k resuscitated pigs. Conclusion: Superior early and 24-hour outcomes were observed with PEG-20k LVR compared to WB and Hextend in a preclinical porcine model of lethal HS, despite decreased OCC from substantial volume-expansion. These findings demonstrate the importance of enhancing microcirculatory perfusion in early resuscitation strategies.